Biosensors: On-line SERS Detection of Single Bacterium Using Novel SERS Nanoprobes and A Microfluidic Dielectrophoresis Device (Small 22/2014) - Lin, Hsing-Ying; Huang, Chen-Han; Hsieh, Wen-Hsin; Liu, Ling-Hsuan; Lin, Yuan-Chuen; Chu, Chia-Chun; Wang, Shi-Ting; Kuo, I-Ting; Chau, Lai-Kwan; Yang, Chiou-Ying (Small (Weinheim an der Bergstrasse, Germany), 2014)
On‐line multiplex SERS detection of pathogenic bacteria is demonstrated at a single‐cell level. On page 4700, L.‐K. Chau, C.‐Y. Yang, and co‐workers prepare SERS nanoprobes via immobilization of antibodies on silica‐coated, dye‐induced aggregate beads of gold nanoparticles (AuNPs). The beads give an enhanced Raman signal due to well‐defined plasmonic hot spots at junctions between AuNPs. In combination with dielectrophoresis, they improve the sensitivity of SERS‐barcode biosensing strategies beyond that of whole‐cell ELISA. The practical detection limit over 10 min is 70 CFU mL−1.